Factors associated with the involvement of women drug users in risky sexual behaviors: A narrative review - Hadis Sourinejad; Mahnaz Noroozi; Fariba Taleghani; Gholam Reza Kheirabadi (Wolters Kluwer Medknow Publications, 2022)
Background: Drug use is known as an important underlying factor in the occurrence of risky sexual behaviors. The present study was conducted to identify the factors associated with the involvement of women drug users in risky sexual behaviors. Materials and Methods: This review was conducted by searching databases of ISI Web of Science, Scopus, Science Direct, Cochrane, PubMed, Scientific Information Database (SID), the Iranian Magazine Database (Magiran), the Iranian Research Institute for Information Science and Technology (IranDoc), and the Iranian Medical Articles Database (IranMedex) and searching through the Google Scholar engine. All the articles published in English and Persian using the keywords including substance use, drug users, addiction, substance use disorders, substance-related disorders, sexual risks, high-risk sexual behavior, HIV risk behavior, unsafe sex, unprotected sex, and risky sex were searched from January 2000 to December 2020. After reviewing the articles, out of 110 articles, 21 articles were selected for final evaluation. Results: Factors related to the involvement of women drug users in risky sexual behaviors were divided into five categories: individual factors, factors related to drug use, inter-personal relationships, gender discrimination, and socio-economic factors. Conclusions: The results can be used in the field of women's social harms in finding strategies and designing the necessary interventions to prevent risky sexual behaviors in women drug users in different societies and cultural contexts. Also, the results can be used by all researchers who want to study the relationship between these factors and the involvement of women drug users in risky sexual behaviors.